Lymphocyte responses to Plasmodium falciparum ring-infected erythrocyte surface antigen (Pf155/RESA) peptides in individuals with naturally acquired Plasmodium falciparum malaria - R. Udomsangpetch (2018)
Antibody titers and lymphocyte responses to synthetic peptides corresponding to repeated amino acid sequences of the 3' and 5' regions of Pf155/ring-infected erythrocyte surface antigen (RESA) were studied in two groups of Thai subjects, soldiers (Rangers), and villagers who differed in their history of malaria exposure. The frequency of Pf155/RESA seropositivity was similar in the two groups while the frequency of high titer antibody was significantly greater in villagers than in Rangers. Lymphocyte responsiveness in vitro to all Pf155/RESA peptides was infrequent for both groups although half of the subjects studied responded to crude Plasmodium falciparum asexual blood stage malaria antigen (MA). Among responders, Pf155/RESA peptides elicited lymphocyte responses in which proliferation and interferon-gamma (IFN-γ) production were not associated, whereas with MA, the two responses were associated. The MA-stimulated lymphocyte proliferation and IFN-γ production for both groups of volunteers appeared to be independent of antibody titer. In this study, antibody, but not lymphocyte, responses to Pf155/RESA peptides were shown to reflect differences in prior exposure and levels of acquired immunity to falciparum malaria.